El presente de subjuntivo en español y la traducción de sus estructuras al árabe (Journal of the College of Basic Education, 2022)
Undoubtedly, the expression of the subjunctive is a communication requirement in any language. The subjunctive mood verbal is considered one of the most difficulties for foreign students. The Spanish subjunctive expresses an attitude of the person about someone or something. It requires another verb that determines the meaning of that attitude. Always indicates a possible and conditional action. It is also used in the imperative form. The subjunctive in Arabic occurs in noun and imperfective of finals, consecutive and secondary sentences. The main objective of this study presents the structures of the present subjunctive in Spanish and Arabic. Besides translation of these structures to Arabic.